Effectiveness of sports massage in reducing hamstring muscle tightness in students with prolonged sitting duration - Alfiansyah, Muchammad Asril; Roepajadi, Joesoef; Noordia, Anna; Nugraha, A. Burhanuddin Kusuma (Sriwijaya Journal of Sport, 2026)
Research Objectives: Students who sit for long periods are at risk of muscle stiffness due to lack of physical activity. This condition can cause hamstring muscle tightness, which reduces flexibility and increases the risk of injury. One intervention that can be used to address this issue is sports massage, which helps relax muscles and reduce muscle tension. Research Objectives: This study aimed to determine the effectiveness of sports massage in reducing hamstring muscle tightness among students with prolonged sitting. Methods: This study employed a quasi-experimental method using a pretest–posttest control group design. The participants were 15 male students from the Department of Nutrition at Universitas Negeri Surabaya (UNESA), cohorts 2023 and 2024. Data were collected by measuring hamstring muscle tightness before (pre-test) and after (post-test) the intervention. Data analysis was conducted using the Wilcoxon Signed Ranks Test to examine within-group differences and the Mann–Whitney U test to compare differences between the experimental and control groups. Results: The experimental group showed a significant difference between pre-test and post-test scores after receiving sports massage treatment, with a mean pre-test score of 25.67 and a mean post-test score of 18.33 (p < 0.05). In the control group, the Wilcoxon Signed Ranks Test also indicated a difference between pre-test and post-test scores (Z = -2.271; Sig. = 0.023), although the treatment did not influence the change. Furthermore, the Mann–Whitney U test revealed a significant difference between the experimental and control groups (p < 0.05). Conclusion: Sports massage is effective in reducing hamstring muscle tightness in students with prolonged sitting duration and can be used as an intervention to improve muscle flexibility and reduce the risk of injury.